KERAGAMAN ISOLAT ACTINOMYCETES BERDASARKAN ANALISIS RFLP TERHADAP GEN NRPS - Nanik Sulistyani (Pharmaciana, 2013)
Actinomycetes is one of the types of microorganisms that is essential forproducing the active compounds, one of which is an antibiotic. Isolation ofActinomycetes from the rhizosphere of rice plant (Oryza sativa L.) and tin plant (Ficuscarica L.) has yielded 13 isolates of antibiotic-producing Actinomycetes. This studyaims to determine the diversity of isolates by RFLP analysis (Restriction FragmentLength Polymorphism) of the NRPS (Non Ribosomal Peptide Synthetase) gene. Thestudy was carried out by isolating Actinomycetes isolate DNA and performed PCR onthe 16SrRNA and NRPS genes. The RFLP analysis of the NRPS gene PCR products isthen performed using the enzyme HaeIII. Identify the presence of DNA, the PCRproduct and RFLP results was performed by agarose gel electrophoresis. The diversityof isolates was analyzed by multivariate analysis. The results showed that the diversityof 13 isolates of Actinomycetes can be grouped into 5 groups: isolates 5 (group 1),isolates 8 (group 2), isolates 11 (group 3), isolates 6,7,9 (group 4) and isolates1,2,3,4,10,12,13 (group 5).